Coffee silverskin as nutraceutical ingredient in yogurt: its effect on functional properties and its bioaccessibility. (25th March 2019) - Bertolino, Marta; Barbosa‐Pereira, Letricia; Ghirardello, Daniela; Botta, Cristian; Rolle, Luca; Guglielmetti, Alessandro; Borotto Dalla Vecchia, Stefania; Zeppa, Giuseppe
Abstract: BACKGROUND: Silverskin is a by‐product obtained from coffee roasting. It is characterized by a high content of dietary fibre, phenolic compounds and caffeine. The aim of this study was to assess the silverskin obtained from two species of Coffea (Arabica and Robusta) at three percentages (2%, 4%, or 6%) into cow whole‐milk yogurt to raise the nutraceutical value of the products and to verify the bioaccessibility of bioactive compounds during the shelf‐life of 3 weeks. RESULTS: The amount and origin of silverskin significantly influenced all the physicochemical parameters. Concerning the bioactive compounds, the highest levels were observed in yogurt supplemented with 6% of silverskin. Between the coffee species, Arabica yielded the highest 5‐caffeoylquinic acid content and the strongest antioxidant activity, whereas Robusta gave the highest caffeine content. The digestion increased antioxidant activity in the yogurt, possibly because of greater accessibility of compounds. CONCLUSION: The results obtained highlighted that silverskin can be used in yogurt production to increase the nutraceutical value of the products and that the bioactive compounds are bioaccessible during the digestion process. The characteristics and bioaccessibility of the resulting yogurt were strongly correlated with the coffee species and with the percentage added. © 2019 Society of Chemical Industry